The Stylistic Value of Some Phraseologisms from I. Creangă and P. Ispirescu’s Fairy Tales - Buzoianu-Ambrinoc, Elvira (Acta Universitatis Danubius. Communicatio, 2023)
Phraseologisms are very important in creating the universe of the fairy tales, because this type of narrative discourse is characterized by specific features. In addition to the fact that they help framing the literary genre, phraseologisms also give expressiveness to the narrative discourse. Most of the expressions are connected to the main themes identified in the fairy tales authored by Ispirescu and Creangă, so they are used in a similar manner in both writers’ works. A slight difference can be noticed in the way Ispirescu necessarily adheres to respect the authenticity of the collected fairy tales, while Creangă creatively distances himself from the literary genre. The beauty of the language they both use is obviously due to the phraseologisms as well.